Pest categorisation of Little cherry pathogen (non‐EU isolates). (18th July 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; Parnell, Stephen; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of non‐EU isolates of the Little cherry pathogen (LCP) for the European Union (EU) territory. LCP is now known to be in fact two distinct, well characterised viruses, Little cherry virus 1 (LChV1) and Little cherry virus 2 (LChV2) collectively referred to here as LChV. Efficient molecular detection assays are available for both viruses but not to discriminate EU and non‐EU isolates. LChV are transmitted by vegetative multiplication of infected hosts and, for LChV2, by mealybug vectors. LChV are reported from a range of countries, both outside and within the EU. Non‐EU isolates are not known to occur in the EU and therefore do not meet one of the criteria for being a Union regulated non‐quarantine pest. The host ranges of LChV are restricted to Prunus species, in particular cultivated and ornamental cherries. LChV non‐EU isolates are listed for some, but not all hosts, in Annex IIAI of Directive 2000/29/EC. LChV isolates are expected to be able to enter and establish in the EU. They have the potential to subsequently spread through plants for planting and, for LChV2, through the action of the Phenacoccus aceris vector, which is present in many EU MS. LChV are able to cause severe symptoms in some cherry varieties while others are less affected. Overall, non‐EU LChV isolates meet all the criteria evaluated by EFSA to qualify as Union quarantine pests. However, given the currently limited impact of EU LChV isolates, the impact of non‐EU isolates, if introduced, could be similarly limited. The main knowledge gaps and uncertainties concern (1) whether EU and non‐EU isolates of LChV might differ in their biology, epidemiology or symptomatology, (2) efficiency of natural spread by vectors under EU conditions and (3) extent of symptoms caused on many EU‐grown varieties.